2009
DOI: 10.4038/cmj.v54i4.1452
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and tobacco use among males in two districts in Sri Lanka

Abstract: Objectives To investigate the prevalence and consumption of tobacco and alcohol among males in the Colombo and Polonnaruwa districts. Design A cross-sectional study based on multistage cluster sampling was carried out in four Medical Officer of Health (MOH) areas in the Colombo (urban) and Polonnaruwa (rural) districts to assess the prevalence of tobacco and alcohol use. The Public Health Midwife areas were considered as primary clusters. The sample consisted of males over 18 years. There were 1318 from the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 6 publications
4
31
3
Order By: Relevance
“…It has been reported that the prevalence of smoking is modestly higher in urban populations (29.9%) than in rural areas (24.4%) of Sri Lanka (13). Considering that our study population is from Ragama, a semi-urban setting, a similar prevalence could be expected.…”
Section: Discussion Prevalence Of Smoking In Schizophreniasupporting
confidence: 53%
“…It has been reported that the prevalence of smoking is modestly higher in urban populations (29.9%) than in rural areas (24.4%) of Sri Lanka (13). Considering that our study population is from Ragama, a semi-urban setting, a similar prevalence could be expected.…”
Section: Discussion Prevalence Of Smoking In Schizophreniasupporting
confidence: 53%
“…A study conducted in two urban and rural districts in the country revealed that the prevalence of current drinking in the urban areas (32.9%) was significantly higher than in rural areas (20.8%) [19]. In literature, there is a paucity of large studies on the epidemiology of alcohol consumption in Sri Lanka, which is a drawback in planning and implementing strategies on alcohol related problems.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 30% of males were alcohol users and prevalence of smoking among males was 26.8%. De Silva et al reported that in 2009 prevalence of alcohol use among males was 32.9% and the prevalence of smoking was 29.9% in urban areas and 24.4% in rural areas [12]. Pathmeswarn et al reported that in 1997 prevalence of alcohol use among the males as 33.3%.…”
Section: Discussionmentioning
confidence: 99%